2022
DOI: 10.5829/ijee.2022.13.02.10
|View full text |Cite
|
Sign up to set email alerts
|

The Strategy of Energy Democracy and Sustainable Development: Policymakers and Instruments

Abstract: Energy democracy policymakers pay attention to planning to the formation of energy markets and exchanges of energy regions, diversification of energy resources, especially renewable resources, and global challenges due to greenhouse gas emissions. Over the introduction of concepts related to sustainable development, energy planning at the international level finds its place and goals in the direction of sustainable development, i.e., economic, social, environmental, and institutional dimensions. Energy democra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 57 publications
0
24
0
Order By: Relevance
“…Increased demand for agricultural products and production resource constraints -especially the limitation of cultivable areas -has made the highest yield per unit area which is the main goal of agricultural producers [1]. Since energy efficiency is a key factor for reaching sustainability [2] and also energy has a direct impact on the efficiency of crop production, a sustainable crop production system needs to be analyzed according to input and output energy to determine the total consumed energy for production per unit area [3].…”
Section: Introductionmentioning
confidence: 99%
“…Increased demand for agricultural products and production resource constraints -especially the limitation of cultivable areas -has made the highest yield per unit area which is the main goal of agricultural producers [1]. Since energy efficiency is a key factor for reaching sustainability [2] and also energy has a direct impact on the efficiency of crop production, a sustainable crop production system needs to be analyzed according to input and output energy to determine the total consumed energy for production per unit area [3].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the sustainability index capability can be successfully applied to provide an overall indicator of the environmental performance of existing applications. That index can allow the above application to support the comparison of competitive options in the strategic decisionmaking process (Esmaeili Shayan et al, 2022) (Niklas & Bera, 2021). 3 The relationship between green ports and smart ports in sustainable development (J.…”
Section: Concepts and Characteristics Of Green Portmentioning
confidence: 99%
“…Numerous practical and theoretical investigations on the performance of FP-SWH have been thoroughly published by Attia et al [1] and Rahmanian et al [2]. Esmaeili Shayan et al [3] reported on the experimental performance of a novel type of flat plate micro-heat pipe array solar water heater. Effective heat gain and thermal efficiency were employed to describe the performance.…”
Section: Greek Symbol Introductionmentioning
confidence: 99%